Andalucía en imágenes: un viaje en el tiempo - Baynat Monreal, Mª Elena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
ABSTRACT We propose a trip along time in three centuries -from the 19th to the 20th century- through the image of Andalusia exported to the travelers in different support media, according to the epoch chosen: etchings in white and black, colour drawings, and paper and digitalised photographs. With this aim in mind we will make a comparative analysis between the illustrations appearing in the French Travel story about Spain by Alexandre Dumas (De Paris à Cadix), from 1847, the pictures and drawings from the book L’Espagne, los provinces du sud, de Séville à Cordoue, written by Octave Aubry and published in 1929, and, finally, the promotional photographs appearing in Andalusia’s official tourism webpage (http://www.andalucia.org/) in 2012. The analysis of the different sources aforementioned, examples from the first half of each century, will lead us to study some coincidences and differences in the image exported to foreign tourists ...